Alumni series: understanding mental health what, when, who, and beyond / Saliha Azlan - Azlan, Saliha (Faculty of Pharmacy, 2023)
What is Mental Health? Mental health is a fundamental aspect of our overall well-being. According to the World Health Organization (WHO), it is defined as "a state of mental well-being that enables people to cope with the stresses of life, realize their abilities, learn well, work well, and contribute to their community." It plays a vital role in our ability to make decisions, build relationships, and shape the world around us. What is Mental Health Disorder? On the other hand, mental health disorders are characterized by clinically significant disturbances in an individual's cognition, emotional regulation, or behavior. These disturbances are typically associated with distress or impairment in important areas of functioning. In short, mental disorders are conditions that significantly affect an individual's mental and emotional well-being. When Does Intervention Become Necessary? The point at which intervention becomes necessary varies from person to person. It often depends on the severity of the mental health disorder and its impact on an individual's life. Common signs and symptoms of mental disorders include significant impairment, disturbances in behavior, emotions, and relationships. Recognizing these signs is crucial to determine when intervention is needed.